THE REGIONAL DIFFERENTIATION OF KNOWLEDGE POTENTIAL IN POLAND IN THE CONTEXT OF BUILDING A KNOWLEDGE-BASED ECONOMY - Wioletta Wierzbicka (Acta Scientiarum Polonorum. Oeconomia, 2018)
The aim of this study was to evaluate the regional differentiation of knowledge potential in Poland and changes which have occurred in this field between 2009 and 2015. The study was based on numerical taxonomy methods, including the linear ordering method. It was concluded that the regional differentiation in knowledge potential in Poland is at a moderate level, and the scale of this differentiation has decreased. This finding has been confirmed by the value of the variability coefficient, which decreased from 22% in 2009 to 17.5% in 2015. The highest level of knowledge potential was identified in Mazowieckie Province. The lowest level of knowledge potential was noted in Lubuskie, Świętokrzyskie and Warmińsko-Mazurskie Provinces.